Synergistic Antioxidant Activity and Optimal Microwave-Assisted Extraction Condition of Caesalpinia sappan L., Hibiscus sabdariffa L., and Clitoria ternatea L. Combinations - Suksaeree, Jirapornchai; Navabhatra, Abhiruj; Wunnakup, Thaniya; Monton, Chaowalit (Trends in Sciences, 2022)
The aims of this work were to evaluate the synergistic antioxidant activity and optimize microwave-assisted extraction of Caesalpinia sappan L., Hibiscus sabdariffa L., and Clitoria ternatea L. combinations. The simplex lattice design was applied to evaluate the synergistic antioxidant activity. The mass ratios of the 3 plants that exhibited synergistic antioxidant activity were further used to investigate the optimal condition of microwave-assisted extraction by Box-Behnken design. Results showed that the synergistic antioxidant activity among the 3 plants: Which was determined by the combination index, was observed at various mass ratios, especially at the equal mass ratio. The optimal microwave-assisted extraction condition providing the best antioxidant activity of the plant extract was microwave power of 300 W for 30 s and 3 cycles. This condition gave the extraction yield of 31.03 ± 0.26 %, total phenolic content of 72.03 ± 3.83 mg GAE/g extract, total flavonoid content of 15.18 ± 0.42 mg CE/g extract, half-maximal inhibitory concentration (IC50) from DPPH assay of 178.16 ± 15.54 µg/mL and IC50 from FRAP assay of 75.26 ± 4.44 µg/mL. The optimal extract showed no toxicity on HepG2 cells although the tested concentration was up to 1 mg/mL with an IC50 value of 5.45 mg/mL. So, a mixture of the 3 colored plants could be used as a supplementary antioxidant product with a safety profile. HIGHLIGHTS Synergistic antioxidant activity was observed among three colored plants The optimal MAE condition was microwave power of 300 W for 30 s and three cycles The optimal extract did not toxic although the tested concentration was up to 1 mg/mL The IC50 of extract on cell viability was 5.45 mg/mL GRAPHICAL ABSTRACT